Optimization of polyphenolic compound extraction as natural antioxidants from pineapple peel waste (Ananas comosus (L.) Merr.) using ultrasonic-cellulase extraction (UCE) method - Kumalaningrum, Amalia Nur; Yosep, Anestasya; Yuniar, Rizka Ayu; Simamora, Gevbry Ranti Ramadhani; Avanza, Mona Rida (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study aimed to optimize the ultrasonic–cellulase extraction (UCE) method for recovering polyphenolic compounds with high antioxidant activity from pineapple peel waste. Pineapple peel is an abundant agro-industrial byproduct containing valuable phenolic compounds with potential applications in functional foods. The extraction process was optimized by varying several parameters, including the solvent-to-sample ratio (10–50 mL/g), enzyme concentration (5–25%), pH (3–7), temperature (30°C–70°C), ultrasonic amplitude (30–70%), and extraction time (30–150 min). The optimal conditions were achieved at a solvent-to-sample ratio of 50 mL/g, enzyme concentration of 15%, pH of 6, temperature of 50°C, ultrasonic amplitude of 70%, and extraction time of 120 min, yielding the highest total phenolic content of 37.80 ± 4.21 mg GAE/g. Comparative analysis showed that the UCE method produced higher polyphenolic content (28.04 ± 1.08 mg GAE/g) and stronger antioxidant activity (IC₅₀ = 9.27 µg/mL) than enzyme-assisted extraction (EAE) or ultrasonic-assisted extraction (UAE) alone. These findings confirm the synergistic effect of ultrasonic cavitation and enzymatic hydrolysis, which enhances the release of bioactive compounds. This study highlights UCE as an effective, green, and energy-efficient technology for transforming pineapple peel waste into natural antioxidants, contributing to sustainable food processing and environmental conservation.